2006
DOI: 10.1074/jbc.m602117200
|View full text |Cite
|
Sign up to set email alerts
|

Transient Activation and Delayed Inhibition of Na+,K+,ClCotransport in ATP-treated C11-MDCK Cells Involve Distinct P2Y Receptor Subtypes and Signaling Mechanisms

Abstract: In C11-MDCK cells, which resemble intercalated cells from collecting ducts of the canine kidney, P2Y agonists promote transient activation of the Na ؉ ,K ؉ ,Cl ؊ cotransporter (NKCC), followed by its sustained inhibition. We designed this study to identify P2Y receptor subtypes involved in dual regulation of this carrier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 49 publications
1
25
0
Order By: Relevance
“…This occurred despite a fall in GFR and suggested that proximal tubular reabsorption was markedly reduced [353]. Ap 4 A can stimulate a number of P2 receptor subtypes, including P2Y 1 and P2Y 4 receptors [331,410], which are both expressed in the rat proximal tubule (P2Y 1 apically, P2Y 4 basolaterally); intravenous delivery of the agonist does not allow differentiation between these possibilities.…”
Section: Renal Tubulesmentioning
confidence: 98%
See 4 more Smart Citations
“…This occurred despite a fall in GFR and suggested that proximal tubular reabsorption was markedly reduced [353]. Ap 4 A can stimulate a number of P2 receptor subtypes, including P2Y 1 and P2Y 4 receptors [331,410], which are both expressed in the rat proximal tubule (P2Y 1 apically, P2Y 4 basolaterally); intravenous delivery of the agonist does not allow differentiation between these possibilities.…”
Section: Renal Tubulesmentioning
confidence: 98%
“…Diadenosine polyphosphates, which influence renal perfusion pressure, activate Cl − and non-selective cation conductance in rat mesangial cells as do ATP and angiotensin II (Ang II); Ap 4 A was the most effective of the dinucleotides [194,318,325]. Diadenosine pentaphosphate (Ap 5 A) and diadenosine hexaphosphate appear to play a regulatory role in mesangial cell proliferation [129].…”
Section: Mesangial Cellsmentioning
confidence: 99%
See 3 more Smart Citations